Early modern Catholicism : essays in honour of John W. O'Malley - O'Malley, John W.; Pabel, Hilmar M., 1964-; Comerford, Kathleen M. (University of Toronto Press, 2001)
The so-called Counter- or Catholic Reformation has traditionally been viewed as a monolith, but these essays decisively challenge this interpretation, emphasizing the variety, vitality, and complexity of Catholicism in the early modern era.